Association Between Ideal Cardiovascular Health and Executive Function in Chinese Primary School Children - Gui, Zhaohuan; Cai, Li; Lv, Yajie; Lai, Lijuan; Zeng, Xia; Chen, Yajun (Frontiers in Public Health, 2022)
Aims: Little information exists on the associations of cardiovascular health, a new metric proposed by the American Heart Association, and executive function, particularly in children. We aimed to explore this topic. Methods: We studied 3,798 children aged 6  12 years from 5 schools in Guangzhou, China. Children’s executive function were evaluated using parent filled questionnaire. We calculated the number of ideal cardiovascular health based on: smoking, body mass index, physical activity, diet, blood pressure, cholesterol, and glucose. Generalized linear mixing model was used to assess the association of the number of ideal metrics and executive function. Results: Compared with children exhibiting ≤ 3 ideal metrics, decreases of 1.37 to 2.63 points in metacognition index and it’s 5 subscale indexes (initiate, working memory, plan/organize, organization of materials, and monitor) were observed in children who attained 5 or ≥ 6 ideal metrics (all p for trend <0.001). Diet and physical activity were independently associated with behavioral regulation index and metacognition index. Conclusions: The number of ideal cardiovascular health was positively associated with performance of executive function in children.